Kepuasan Kerja Memediasi Pengaruh Kompensasi dan Motivasi Terhadap Kinerja Pegawai: Studi Pada Pegawai Non PNS Tenaga Kependidikan Bagian Pelayanan Administrasi Subbag Rumah Tangga di Universitas Negeri Malang - Rara Aditi Inandriciya; Endang Suswati; Jose Rizal Joesoef (Warta Pendidikan | e-Journal, 2021)
The purpose of this study was to analyze the effect of compensation and motivation on employee performance through job satisfaction. The type of research used is explanatory research. The population of this study was 45 Non Civil Servants' Educational Personnel Administration Household Subdivision Services with a sampling technique used saturated sampling. The results showed compensation had a positive and significant effect on job satisfaction; compensation has a positive and significant effect on employee performance; motivation has a positive and significant effect on job satisfaction; motivation has a positive and significant effect on employee performance; job satisfaction has a positive and significant effect on employee performance; compensation has a significant effect on employee performance through job satisfaction; and motivation has a significant effect on employee performance through job satisfaction.